Decision-making factors of older adults with end stage renal disease toward renal placement therapy - Somboontanont, Wilaipun; Thongterethum, Natma; Srisuntorn, Pensiri; Sanseha, Ladda; Sritippayawan, Suchai (Journal of Public Health Nursing, 2025)
This mixed methods research was aimed to study factors related to decision-making experience of renal placement therapy among elders with end stage renal disease. The participants in this study were 82 elders with end stage renal disease receiving renal placement therapy. Data were collected using in-depth interviews, perception of illnesses questionnaire and perceive of social support questionnaire. Descriptive statistic and Pearson’s product-moment correlation coefficient were used to analyze data. The content analysis was applied to analyze qualitative data. Study revealed that Glomerular filtration rate (GFR) had a statistically significant positive association with age (r=0.245, p ≤ 0.01). Perception of illnesses had a relationship with education level and perceive of social support (r= 0.226, 0.347, p ≤ 0.05). Perceive of social support had a statistically significant relationship with education level (r= 0.260, p ≤ 0.05) and age (r= -0.225, p ≤ 0.05). Elders’ decision-making experience of renal placement therapy for end stage renal disease were categorized into three main aspects: 1). Experiences before making decision consisted of two sub-themes: the perception of seriously ill, close to death, and had no other options; and prolonging one's life, 2) Decision- making factors toward renal replacement therapy consisted of two sub-themes: the best available treatment and the decision time depends on many factors, and 3) Experiences after decision making. Patients experience stress after renal replacement therapy due to costs and lifestyle changes. The findings of this study provided a vivid and better understanding of first decision-making experience of renal placement therapy from elders with end stage renal disease perspectives. This information is crucial for planning interventions relevant to elders’ perspective as well as to ease up the difficulty time according to the renal replacement therapy plan.